Delayed Mitogenic Stimulation Decreases DNA Damage Assessed by Micronucleus Assay in Human Peripheral Blood Lymphocytes after 60CO Irradiation. Issue 3 (1st July 2014) - Selvan, G. Tamizh; Bhavani, M.; Vijayalakshmi, J.; Solomon, F.D. Paul; Chaudhury, N.K.; Venkatachalam, P.
While contradictory reports are available on the yield of dicentric chromosomes (DC) in blood samples stored at different temperature and stimulated to enter into cell cycle, various times gap followed by exposure, limited information is available on the micronucleus (MN) assay. As scoring the micronuclei frequency from the blood lymphocytes of exposed individuals is an alternative to the gold standard DC assay for triage applications, we examined radiation induced MN yield in delayed mitogenic stimulation after irradiation of in vitro . Peripheral blood lymphocytes (PBL) were exposed to low LET ( 60 Co) radiation dose (0.1 to 5Gy) and incubated at 37°C for 2, 6 and 24 hours. The MN frequency obtained in blood samples stimulated 2 hours post-irradiation showed a dose dependent increase and used to construct the dose-response curve. Further, the results also showed that blood samples stimulated twenty four hours of post-irradiation, a significant reduction (p<0.05) in MN frequencies were obtained when compared to that of blood samples stimulated two hours and six hours after post-irradiation (0.5, 1, 3 and 5Gy). The observed result suggests that the prolonged PBL storage without mitogenic stimulation could lead to interphase cell death and a delayed blood sampling could results in underestimation of dose in biological dosimetry.